Infant Sex Moderates the Effects of Maternal Pre‐ and Postnatal Stress on Executive Functioning at 8 Months of Age. (11th August 2017) - Nolvi, Saara; Pesonen, Henri; Bridgett, David J.; Korja, Riikka; Kataja, Eeva‐Leena; Karlsson, Hasse; Karlsson, Linnea
Abstract : Previous studies report that early life stress, including maternal pre‐ and postnatal stress, has adverse effects on cognitive development and that these associations might be sex‐specific. However, no studies exist on early life stress and infant executive functioning (EF). The aim of this study was to examine the relationship between maternal pre‐ and postnatal stress and infant EF, and whether these associations are moderated by infant sex. Maternal prenatal depressive, general anxiety, and pregnancy‐specific anxiety symptoms were measured three times, and postnatal depressive and general anxiety symptoms were measured 6 months postpartum. Infant EF was assessed with a modified A‐not‐B task 8 months postpartum ( N  =   214). Maternal postnatal general anxiety predicted poorer EF in girls in comparison with boys. Moreover, there was a trend toward an interaction between prenatal anxiety and infant sex such that prenatal anxiety predicted infant EF differently in girls and in boys. No association was found between depressive symptoms or pregnancy‐specific anxiety symptoms and infant EF. These findings suggest that maternal anxiety may have sex‐specific effects on early EF and that pre‐ and postnatal stress may differently affect infant EF/cognitive development. The implications of these findings and important future directions are discussed.